THE ROLE OF ECONOMIC LAW IN ADAPTING TO GLOBALISATION AND TECHNOLOGICAL ADVANCEMENTS: A LITERATURE REVIEW - Gunawan Widjaja (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study examines the role of economic law in adapting to globalisation and technological advancement through a literature review. Globalisation and the development of digital technology have brought about significant transformations in the dynamics of the global economy, requiring rapid, responsive, and innovative legal regulatory adaptation. Economic law functions as a normative framework that regulates trade, investment, consumer protection, and transaction security in the modern era. Through a literature review, this study identifies the main challenges faced by economic law, such as harmonisation of regulations between countries, personal data protection, regulation of the digital economy, and inclusiveness in economic development. This study also emphasises the importance of adaptive and harmonious legal reforms to maintain legal certainty, encourage innovation, and ensure social justice and sustainable economic development. The results of this study are expected to serve as a basis for policymakers and legal practitioners in formulating relevant and progressive economic law development strategies amid the tide of globalisation and technological revolution.